The Concept Assignment Problem in Program Understanding - Biggerstaff, Ted J.; Mitbander, Bharat G.; Webster, Dallas (Institute of Electrical and Electronics Engineers, Inc., 1993)
A person understands a program because they are able to relate the structures of the program and its environment to their human oriented conceptual knowledge about the world. The problem of discovering individual human oriented concepts and assigning them to their implementation oriented counterparts for a given program is the concept assignment problem. We will argue that the solution to this problem requires methods that have a strong plausible reasoning component. We will illustrate these ideas through example scenarios using an existing design recovery system called DESIRE. Finally, we will evaluate DESIRE based on its usage on real-world problems over the years.